Social entrepreneurship, social entrepreneur and social enterprise : a review of concepts, definitions and development in Malaysia / Mohd Ali Bahari Abdul Kadir and Suhaimi Mohd Sarif. - Abdul Kadir, Mohd Ali Bahari; Mhd Sarif, Suhaimi (Universiti Teknologi Mara Selangor, 2016)
A decade ago the concept of social entrepreneurship was rarely discussed in Malaysia even though the practice of delivering social values to the population has been around for years. Efforts that combined the concept of entrepreneurship and social development were established years before the emergence of the term. Only in recent years the concept of social entrepreneurship is making a significant breakthrough and attaining more interest not only from social entrepreneurs but also academics and policy makers due to globalized economic system that in turn has resulted in the emergence of social entrepreneurship within a complex framework of political, economic and social changes occurring at the global, national and local levels. Nevertheless, the concept and definitions of social entrepreneurship, social entrepreneur and social enterprise need to be comprehended by those who are involved in the sector to further sustain the development of pertinent initiatives. Therefore, this paper reviews current literature pertaining the concepts and definitions of social entrepreneurship, social entrepreneur and social enterprise and recent development of the sector in Malaysia.